2016
DOI: 10.1097/shk.0000000000000607
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Islet Responses to Metabolic Trauma

Abstract: Carbohydrate, lipid, and protein metabolism are largely controlled by the interplay of various hormones, which includes those secreted by the pancreatic islets of Langerhans. While typically representing only 1–2% of the total pancreatic mass, the islets have a remarkable ability to adapt to disparate situations demanding a change in hormone release, such as peripheral insulin resistance. There are many different routes to the onset of insulin resistance, including obesity, lipodystrophy, glucocorticoid excess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 120 publications
0
21
0
Order By: Relevance
“…Because pancreatic islets expand during states of insulin resistance, 21 we measured insulin-positive cell area, indicative of the pancreatic b-cell population, in response to the corticosterone intervention. Insulin-positive area increased by 2.1-fold in corticosterone-treated mice ( Figure 6, A and B).…”
Section: Corticosterone Enhances Pancreatic Islet Insulin-positive Armentioning
confidence: 99%
“…Because pancreatic islets expand during states of insulin resistance, 21 we measured insulin-positive cell area, indicative of the pancreatic b-cell population, in response to the corticosterone intervention. Insulin-positive area increased by 2.1-fold in corticosterone-treated mice ( Figure 6, A and B).…”
Section: Corticosterone Enhances Pancreatic Islet Insulin-positive Armentioning
confidence: 99%
“…In healthy individuals, there is a feedback loop between insulin-sensitive tissues and the β-cells in that an increase in peripheral insulin demand is augmented by insulin secretion. Thus, changes in the peripheral insulin sensitivity are reciprocally compensated by changes in circulating insulin levels [ 98 , 99 ]. Failure in this reciprocal loop may result in the disruption of glucose homeostasis and deviations from normal glucose tolerance to the development of glucose intolerance ( Figure 1 ) and, at the extreme, T2DM [ 97 ].…”
Section: Effects Of Gc Excess In the Pancreatic Islets: Contributimentioning
confidence: 99%
“…As a result, insulin insufficiency and pathologic changes in insulin release can develop, which could lead to worse outcomes. 11 For example, Bhayani and colleagues, 12 in their research on MetS and liver resections, found a 5-fold increase in MI, a 2-fold increase in pulmonary complications, and a 70% increase in surgical site infections in patients with the syndrome. We also noted significantly higher rates of acute kidney injury, ARDS, cardiac arrest, decubitus ulcers, MI, unplanned admission to the ICU, unplanned intubations, and severe sepsis in MetS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The peripheral insulin resistance seen after severe trauma could be opposed by blocking the renin-angiotensin system to improve glucose use in patients already struggling with MetS. 11 In addition, the future of precision medicine in the field of metabolomics has vast potential for these patients. By identifying unique molecular characteristics of a person with MetS at the time of initial trauma, clinicians at the point of care may eventually be able to predict an individual's clinical course, facilitating more timely, individualized treatment, ultimately improving outcomes.…”
Section: Discussionmentioning
confidence: 99%